Musculoskeletal disorders in nurses who provide home care - Carneiro, P. (2010)
Work related musculoskeletal disorders (WRMSDs) have been described as the most important occupational health problem tormenting the nursing workers. This work demonstrated a preliminary analysis on the evaluation of responses to a questionnaire based on one developed by Kuorinka and colleagues. Main goal of this work is the characterisation and evaluation of the risk of WRMSDs on the home care nursing. The first results reveal that a great percentage of the respondents provide home care. The most frequent complaints are in spine and shoulders. There are no significant association between the related disorders and the home care